Development and Characterization of Nanoliposomal Hydroxyurea Against BT-474 Breast Cancer Cells - Akbari, Azam (Adv Pharm Bull, 2020)
Purpose: Hydroxyurea (HU) is a well-known chemotherapy drug with several side effects which limit its clinical application. This study was conducted to improve its therapeutic efficiency against breast cancer using liposomes as FDA-approved drug carriers. Methods: PEGylated nanoliposomes-containing HU (NL-HU) were made via a thin-film hydration method, and assessed in terms of zeta potential, size, morphology, release, stability, cellular uptake, and cytotoxicity. The particle size and zeta potential of NL-HU were specified by zeta-sizer. The drug release from liposomes was assessed by dialysis diffusion method. Cellular uptake was evaluated by flow cytometry. The cytotoxicity was designated by methyl thiazolyl diphenyl-tetrazolium bromide (MTT) test. Results: The size and zeta value of NL-HU were gotten as 85 nm and -27 mV, respectively. NL-HU were spherical.NL-HU vesicles were detected to be stable for two months. The slow drug release and Weibull kinetic model were obtained. Liposomes considerably enhanced the uptake of HU into BT-474 human breast cancer cells. The cytotoxicity of NL-HU on BT-474 cells was found to be significantly more than that of free HU. Conclusion: The results confirmed these PEGylated nanoliposomes containing drug are potentially suitable against in vitro model of breast cancer.